Effect of volume fraction on flow properties for centrifugal pumps for mixed flow (University of Thi-Qar Journal for Engineering Sciences, 2022)
The performance of a centrifugal pump employing a single-step centrifugal pump under a gas-liquid mix and with a single suction pump is displayed. volume fracture ratios, IGVF % (1,5,10,15) 2compared with the flow rate Q/Qdes,w (8-1,2), the experimental and numerical simulations have been compared. The findings are presented by coefficients without dimensions from the similarity law. The computational results have shown that the nominal rotational velocity of numerous flow parameters has achieved good agreement on the experimental data, with the degradation in the head being noticed step by step, i.e. the bigger the volume ratios, the more the head deterioration is. The coefficient of inflow declines.